Artemia enrichment as modulator of gene expression patterns of Enteroctopus megalocyathus paralarvae at pre-settlement stage - Uriarte, Iker; Enriquez, Ricardo; Hernandez, Jorge; Espinoza, Viviana; de Oca, Marco Montes; Silva, Andrea X.; Monroig, Oscar; Sanchez, Patricio; Alvarez, Diego; Farias, Ana; Romero, Alex (My University, 2024)
Enteroctopus megalocyathus, the Patagonian red octopus, is the only octopus species for which a complete pro-duction cycle in captivity has been accomplished in Chile. The rearing of E. megalocyathus paralarvae from hatching to the settlement of juveniles lasts 90 days and it represents the bottleneck in the culture of this species. The paralarval stages from 1 to 60 days after hatching (DAH) are fed on enriched Artemia while, when pre -settlement behavior appears, from 60 DAH onwards, the feeding protocol is a mixed diet of enriched Artemia and juvenile marine crabs. Marine crustaceans represent a suitable diet to improve E. megalocyathus paralarvae survival, complementing the enriched Artemia to feed the pre-settling paralarvae. To determine the effect of Artemia enrichment on the response of E. megalocyathus at the pre-settling paralarval stage, paralarvae were fed two mixed diets containing juvenile marine crabs (Petrolisthes spp.) and differing only in Artemia enrichment: enriched (complete diet, CD), or unenriched (limited diet, LD). After 30 days of feeding trial, samples consisting of whole paralarvae were collected for transcriptomic analysis using high-quality total RNA to generate six mRNA libraries (two treatments x three biological replicates). A total of 270 genes were differentially expressed between paralarvae fed LD and those fed CD. When classifying the cellular processes in which the genes of LD and CD paralarvae differed significantly, it was observed that the downregulated/upregulated gene ratio was 2/1 in genes related to membrane organization and neuron differentiation. The genes of paralarvae fed a LD for which upregulation was equal to or >20 times compared with those fed a CD were related with increased rearrangement of tissues, molecular transport, energy production, improvement of sensory organs, cellular processes, transcription, and protein catabolic processes. The downregulated genes in paralarvae fed a LD were involved with reduced DNA repair and mRNA replication and elongation, molecular transport, cellular protein modification, cellular component organization, inflammatory cytokines, and biosynthetic processes. It was concluded that removing enrichment from Artemia, even under co-feeding with marine crustaceans, results in notable changes in the transcription that, while not generating a significant detriment to growth in 30 days of experimentation, could affect subsequent growth phases.
Keywords: enteroctopus megalocyathus; pre-settling paralarvae; transcriptomics; enriched artemia; marine prey